2021
DOI: 10.3389/fneur.2021.722526
|View full text |Cite
|
Sign up to set email alerts
|

Age-at-Injury Determines the Extent of Long-Term Neuropathology and Microgliosis After a Diffuse Brain Injury in Male Rats

Abstract: Traumatic brain injury (TBI) can occur at any age, from youth to the elderly, and its contribution to age-related neuropathology remains unknown. Few studies have investigated the relationship between age-at-injury and pathophysiology at a discrete biological age. In this study, we report the immunohistochemical analysis of naïve rat brains compared to those subjected to diffuse TBI by midline fluid percussion injury (mFPI) at post-natal day (PND) 17, PND35, 2-, 4-, or 6-months of age. All brains were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 108 publications
(147 reference statements)
6
25
0
Order By: Relevance
“…Approximately 60–120 min after surgery, rats were subjected to mFPI with methods we have previously described for PND17 and PND35 rats ( 13 , 23 , 24 ). Rats were re-anesthetized with 5% isoflurane in 100% oxygen delivered for 3 min.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Approximately 60–120 min after surgery, rats were subjected to mFPI with methods we have previously described for PND17 and PND35 rats ( 13 , 23 , 24 ). Rats were re-anesthetized with 5% isoflurane in 100% oxygen delivered for 3 min.…”
Section: Methodsmentioning
confidence: 99%
“…The hub assembly on the skull was filled with saline and attached to the FPI device (custom design and fabrication, Virginia Commonwealth University, Richmond, VA). When a toe pinch withdrawal response was detected, the pendulum was released causing a fluid pulse directly onto the dura resulting in a mild to moderate brain injury in all rats [PND17 = 1.5 atmospheres pressure (atm), PND35 = 1.9 atm] ( 13 , 23 , 24 ). Sham rats were connected to the device, but the pendulum was not released.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Doust et al, found that aged rats (10 months), that had received a recent (2, 4, or 6 months) moderate mFPI had increased dendrite neurofilament pathology and higher CD68 activity in microglia. Additionally rats that received the brain injury earlier in life (PND 17–35) had higher colocalization between TREM2 and microglia in the hippocampus (Doust et al, 2021 ). These indicate that age at time of injury impacts neuropathology but even brain injuries received earlier in life can continue to interact with aging neuroinflammation.…”
Section: Age-related Inflammationmentioning
confidence: 99%